Sosialisasi Inovasi Pembelajaran Matematika SMA Melalui Media Pembelajaran Trigonometri - Vinsensius H Ndori; Tanti Diyah Rahmawati; Erwin Prasetyo; Salmawaty Salmawaty; Maria Aprilia Venerani Gokun (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Mathematics is a learning whose material is abstract. This causes students to find it difficult to understand mathematics, feeling that mathematics is difficult and boring. This condition occurred at Karitas Watuneso Vocational School. This Community Service aims to provide socialization and innovation in mathematics learning using trigonometry as a medium so that it is hoped that students will be more able to understand and be interested in learning mathematics. The results of the service with questionnaires that have been filled in by students show that the use of trigonometry teaching aids in their learning is 85% strongly agree and 15 percent agree, the method of delivering the material is 88% strongly agree and 12% agree, and students' understanding of the use of learning media is 80% strongly agree and 20% agree, while how to use it, 85% strongly agree and 15% agree. Thus, it can be concluded that students feel that the use of trigonometry teaching aids can facilitate students' understanding of trigonometry material and students are enthusiastic in this activity.